PENYESUAIAN DIRI MAHASISWA PERANTAU DENGAN LATAR BELAKANG PERCERAIAN ORANGTUA - Auliana Sabbilla; Untung Subroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Parental divorce is an event that can have a significant psychological impact on children, especially during adolescence and young adulthood. Changes in family structure, emotional dynamics, and potential post-divorce conflicts are often challenges that children must face. For migrant students, these challenges are even more complex as they must also adapt to a new environment away from their families, with different academic and social demands. Migrant students often face the challenge of adapting to a new environment that is socially and culturally different, including students who have divorced parents and choose to migrate. Parental divorce can worsen their emotional condition, adding to the psychological burden that must be faced when migrating. This study aims to look at the description of self-adjustment in migrant students who experience parental divorce. This study uses qualitative methods with interview and observation data collection. The subjects of this study consisted of 6 participants. From the six research participants, it can be concluded that 2 participants can pass 5 dimensions of self- adjustment, namely perception of reality, ability to cope with stress and anxiety, positive self-image, ability to express emotions well, and good interpersonal relationships. While the other 4 participants could not pass some dimensions of self-adjustment, namely perception of reality, positive self-image, and ability to express emotions well.